Trends in Islamic Education Policy Research Based on Bibliometric Study and Network Analysis in Scopus Database: Tren Riset Kebijakan Pendidikan Islam Berdasarkan Kajian Bibliometrik dan Analisis Jaringan di Basis Data Scopus - Khumayroh, Desy; Lismawati, Lismawati (Halaqa: Islamic Education Journal, 2025)
This study aims to analyze the development and trends of Islamic education policy research indexed in the Scopus database through a bibliometric approach. The focus of the study was directed at keyword mapping, author networks, institutional affiliations, and countries of origin of publications. The method used is bibliometric analysis with the help of VOSviewer, RStudio, and Microsoft Excel software to process publication metadata in the period 1974 to 2025. The results show that Indonesia is the country with the highest number of publications, followed by Iran and Malaysia. The trend of publications increased sharply after 2020, and the dominant keywords that emerged reflected the focus on curriculum, educational policies, as well as the integration of Islamic values in contemporary education. The theoretical contribution of this study lies in its unique approach, namely the use of bibliometric methods that have not been widely applied in the context of the study of Islamic education policy. This approach allows for a systematic and data-driven mapping of knowledge structures. Practically, these findings can be used by policy designers, managers of Islamic educational institutions, and curriculum developers as a reference in formulating strategies and policies that are adaptive to global scientific trends. However, this study has limitations in the scope of the data, which only includes English-language articles and the types of documents in the form of journal articles available at Scopus, so it is not fully representative of the entire global literature. Nevertheless, the results of this study are expected to contribute to the development of Islamic education policy strategies that are more adaptive to the times. Highlights: Rising Trends: Islamic education policy publications surged after 2020, with Indonesia leading in output. Research Focus: Dominant keywords highlight themes like curriculum, policy, and integration of Islamic values. Methodological Contribution: Utilizes bibliometric analysis—rare in this field—for systematic knowledge mapping. Keywords: Bibliometric, Policy, Islamic Education, VOSviewer